Вы находитесь на странице: 1из 3

S

F nds = F ds = divF dv = F dv =

¯

S

B

Q

v

S

F nds = div F dv

¯

B

dM + dN + dR

dx

dy

dz

dv

R 2 S F nds = B div F dv

¯

C

(P dx + P dy) =

R

dP + dQ

dx

dy

dA

S F nds F = 2xy ¯ i + yz 2 j + xz k

¯

¯

S

F nds =

v

dP

dx

+ dQ + dR

dy

dz

dv

d(2xy)

dx

d(yz 2 ) dy

+ d(xz)

dz

+

dzdydx

312

000

(2y + z 2 + x)dxdydz

31

00

(4y + 2z 2 + 2)dydz

3

0

(4 + 2z 2 )dz = 4z + 2

3 z 3 | 0 = 30

3

63

00

6

0

03 6x

2

000

(2y + z 2 + x)dxdydz

6y xy + (6 x) 3

24

+ 3x x 2 dydx

2

27 9x

2

+ (6 x) 3

8

+ 9x 9x 2 dx

2

= 81/2

S F nds F = 4xz ¯ i y 2 j + yz k

¯

¯

− x ) 3 8 + 9 x − 9 x 2 dx 2 = 81

S

F nds =

v

dP

dx

+ dQ + dR

dy

dz

dv

d(4xz)

dx

d(y 2 ) dy

+ d(yz)

dz

+

dzdydx

111

000

(4z 2y + y)dxdydz

S

1

0

11

00

(4z y)dydz

4z 1 2 dz = 3

2

F nds = F nF ndxdz/ | nj |

11

00

(y 2 )dydz

1

0

(y 2 )dz = (y 2 )

pero

y = 1 = 1